First report of tomato mosaic tobamovirus from Malaysia - Abdul Samad, Norani; M., Singh; Yusoff, Khatijah (Universiti Putra Malaysia Press, 1996)
A mosaic disease of tomato was observed in Cameron Highlands, Malaysia and a tobamovirus was implicated as the cause based on virus particle morphology and reproduction of symptoms in Lycopersicon esculentum Mill. The virus was identified as tomato mosaic tobamovirus (ToMV) based on host range and serological properties.